THE GUERRILLA’ NOVEL IN MEXICO AND THE ART OF “PULLING TRICKS” (Andamios, Revista de Investigación Social, 2011)
This article tackles fiction narratives of production sociologically speaking, on which the main theme are urban “guerrillas” from the 70’s in the 20th century in Mexico. Their main purpose is to expose how these narratives jeopardize the muted logic imposed from the dominant speeches related to that period so they can be incorporated in today’s present life like symbols which the result lays in historic gaps thus becoming on legible spaces, for they play, while on reading them, a call up roll of the social representations about urban “guerrillas”. Our propound comes that fiction literature is, layed under a particular thought escaping from politics and scientific reasoning, a power which embeds on the reader`s desire so as in space and historical time.
Keywords: Insinuer; mimesis/poiesis; polyphony; chronotope; likelihood; tactical; strategy